PRESERVATION OF FISH BY FREEZING AND GLAZING: I L KE PING QUALITY OF FISH WITH PARTICULAR REFERENCE TO YELLOW DISCOLOURATION AND OTHER ALLIED ORGANOLEPTIC CH.ANGES ON PROLONGED STORAGE - JADHAV, M G; MAGAR, N G (Fishery Technology, 2025)
Organoleptic observations of quick, slow and bloclc frozen, glazed and stored fish were recorded at regular intervals. Glazing was renewed at intervals of four weeks. Development of yellow discolouration in the case of white pomfret was followed. Keeping quality of glazed fish was better than unglazed frozen fish. Yellow discolouration could be controlled by ascorbic acid for 4 months and by a mixture of odium chloride and glucose for 5t months.